Assessment of disability caused by rheumatic diseases in general practice. Issue 8 (August 1987) - Sullivan, F M; Eagers, R C; Lynch, K; Barber, J H
Abstract : At present general practitioners lack a tool for defining the level of disability of individual patients and groups of patients with arthritis. An assessment technique (health assessment questionnaire) developed in the United States is described, and its use in general practice evaluated. Sixty two patients agreed to be visited at home to compare their observed abilities when performing the tasks of the health assessment questionnaire. The health assessment questionnaire (HAQ) is easily understood and takes patients only 10-15 minutes to complete. The numerical scores (range 0-3) for disability obtained on the postal questionnaire are close to the observed scores when patients are visited at home.